A study on unmet need of family planning among married tribal women in a rural area in Eastern India during COVID-19 pandemic - Archi Chandra; Sankar Nath Jha; Rituparna Ray (Wolters Kluwer Medknow Publications, 2023)
Background: COVID-19 has impacted health system worldwide including family planning, acting as a major hindrance in the way of population control. This study is conducted to assess the unmet need of family planning among married tribal women, various reasons behind it, and its relation with sociodemographic variables during COVID-19 pandemic. Materials and Methods: This cross-sectional study was conducted in Burda village of Purulia district of West Bengal in Eastern India. A sample size of 80 was calculated. Study subjects, who fulfilled our inclusion criteria, were selected using simple random sampling from the list of eligible couples which was obtained from ASHA. After obtaining ethical clearance from the Institutional Ethics Committee, permission from panchayat of Burda village, and consent from the study subjects, they were interviewed using a pretested, predesigned, and semi-structured schedule. Data were entered into MS Excel and analyzed using IBM SPSS version 20.0 version (Armonk, NY, USA: IBM Corp.). Results: 81.2% were willing to use family planning methods; among them, 80% stated media as their prime source of information. 68.6% had used male condoms as a method of family planning. 82.4% stated government health-care facility as their source of availability of family planning methods. Unmet need of family planning among the study subjects was 17.5%. Major reason for nonuse of family planning methods was that they did not take anything from health-care providers due to fear of getting COVID-19 infection. Bivariate analysis showed a significant association of unmet need of family planning with educational status of husband (P = 0.023, odds ratio [OR] = 4.211) and type of family (Fisher's exact significance = 0.047, OR = 7.719). Conclusion: Unmet need of family planning among tribal population is still high during this pandemic, and the causes are needed to be acted upon.